Dynamisk Åtkomstkontroll För Kontorsnätverk : En genomgång av åtkomstkontroll med betoning på zero trust och NIS 2 - Downey, Wyatt (Luleå tekniska universitet, Institutionen för system- och rymdteknik, 2025)
This thesis examines how dynamic access control can be implemented with a focus on zero trust architecture.The thesis reviews how companies with larger office networks, like Skellefteå Kraft AB can achieve upcomingNIS 2 requirements. The thesis explains logging, authentication and dynamic access control and how thesecan help achieve a secure network that is ready for NIS 2.The work begins by explaining how dynamic access control works and important elements of the zero trustmodel. It goes on to explain how identification and authentication are associated with identity and accessmanagement systems such as Active Directory and multi factor authentication.Then network segmentation is explained and how it can be used to divide a larger network, and why it shouldbe done from a security standpoint.Methods for the work included research, interviews and weekly reports to supervisors at Luleå University ofTechnology, as well as Skellefteå Kraft.The result shows that an effective implementation of zero-trust requires careful planning, and how this can beachieved. It also describes the use case and implementation of dynamic access control, and how it can be used tomanage access. By using these systems and guidelines, Skellefteå Kraft can be well prepared for the upcomingNIS 2 directive.